NAUTILUS: A CASE STUDY IN HOW A DIGITAL SCORE CAN TRANSFORM CREATIVITY. (January 2023) - Vear, Craig; Rees, Carla; Stephenson, Adam
Abstract: This article discusses Nautilus (2022), a composition for solo bass flute created using machine-learning techniques and a Unity game engine. We consider the approaches we adopted and how they enhanced creativity and musicianship for those involved. We reflect on Unity's potential as a novel and flexible driver for the creation of a musical score in which traditional elements of compositional design are presented to a performer as a co-creator for interpretation and communication inside the act of musicking. Through this we offer insights into performer agency and how a performer decodes media, sound, images and AI through their instrument, personal skills and musical aesthetic. We describe how the notion of a music score was re-conceptualised, transforming our understanding of the activities of composition, collaboration and performance.